Soy milk intake and plasma sex hormones: a cross-sectional study in pre- and postmenopausal women (EPIC-Oxford). - Verkasalo, P; Appleby, P; Davey, G; Key, T (2001)
Soy beans contain high levels of the isoflavones genistein and daidzein and their glucosides. We investigated the relationship between soy milk intake and plasma concentrations of estradiol, sex hormone-binding globulin, and, in premenopausal women, follicle-stimulating hormone, luteinizing hormone, and progesterone in a cross-sectional study of 636 premenopausal and 456 postmenopausal British women. Sixty-five percent of the women were vegetarians or vegans. Data on soy milk intake and other factors were obtained from a validated food frequency questionnaire, hormone concentrations were measured by immunoassays, and variations in geometric means were compared using analysis of covariance. We observed no statistically significant trends or meaningful associations between soy milk intake and circulating sex hormones. Adjusting for factors possibly affecting circulating hormone concentrations did not materially alter the results. We conclude that soy milk intake does not change plasma concentrations of sex hormones in pre- or postmenopausal British women who consume soy milk as a part of their regular diet.